Comparative Study of Student Learning Achievement through Different Admission Method of B.Ind.Tech. program, Faculty of Industrial Technology and Management, KMUTNB - Srikamta, Jumrean (Food Agricultural Sciences and Technology, 2019)
This research aimed to study and compare student learning achievement through different admission methods, the proportion of graduation and the proportion of drop out student. Student groups are from the undergraduate students of Bachelor of Industrial Technology (Information Technology for Industry) program, Faculty of Industrial Technology and Management, King Mongkut’s University of Technology North Bangkok. It was carried out by studying a population of 413 enrolled students from 2011-2016. The study used the statistics of frequency, percentage moreover, analyze and compare the grade point average (GPA) with One-Way ANOVA statistics and then using the Scheffe’s test method to find out which pairs of means are significant. After that using Chi-Square statistics method for comparative analysis of the proportion of graduation and dropout students. The study indicated that the GPA of the first-year student with different enrollment methods is different with statistically significance (Sig=.00). When considering the differences between pairs, found that the group of student from outstanding achievement are the difference from a group of direct admission with statistical significance (Sig=.00), a difference from district quota (Sig=.00) and difference from other admission systems (Sig=.03). The study of the academic results when graduating with different enrollment methods are different with statistically significance (Sig=.03). And the outstanding achievement group has a different academic result when graduating with direct admission group (Sig. = .04). And the proportion of graduation and dropout is the difference with statistical significance (Sig =0.00). The group of student from outstanding achievement has the highest number of graduation (90.5%), graduate on time (34.5%) and the lowest number of dropout (9.5%).